2012
DOI: 10.1186/1752-153x-6-17
|View full text |Cite
|
Sign up to set email alerts
|

Biomedical properties and preparation of iron oxide-dextran nanostructures by MAPLE technique

Abstract: BackgroundIn this work the chemical structure of dextran-iron oxide thin films was reported. The films were obtained by MAPLE technique from composite targets containing 10 wt. % dextran with 1 and 5 wt.% iron oxide nanoparticles (IONPs). The IONPs were synthesized by co-precipitation method. A KrF* excimer laser source (λ = 248 nm, τFWHM≅25 ns, ν = 10 Hz) was used for the growth of the hybrid, iron oxide NPs-dextran thin films.ResultsDextran coated iron oxide nanoparticles thin films were indexed into the spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 50 publications
1
41
0
Order By: Relevance
“…11,17,19,28,36 However, the use of magnetic nanoparticles in CaP scaffolds for bone tissue engineering applications is rarely reported. In the current work, Fe 2 O 3 nanoparticles with the size of <50 nm were added to TCP precursors to achieve the Fe-doped TCP scaffolds.…”
Section: 0 Introductionmentioning
confidence: 99%
“…11,17,19,28,36 However, the use of magnetic nanoparticles in CaP scaffolds for bone tissue engineering applications is rarely reported. In the current work, Fe 2 O 3 nanoparticles with the size of <50 nm were added to TCP precursors to achieve the Fe-doped TCP scaffolds.…”
Section: 0 Introductionmentioning
confidence: 99%
“…Nowadays, materials science has reached a stage of development that makes it possible to synthesize new engineered particles at a nanometric scale and to control their properties. Thus, tailoring the properties of nanoparticles for suitable biomedical, environmental, and industrial applications is one of the most studied areas of research worldwide [1][2][3]. Ideal candidates for developing nano-engineered structures with improved properties by functionalization are inorganic materials.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the intensity of the bands corresponding to the maghemite γ-Fe 2 O 3 phase increases with increasing NPs concentration in the composite targets used in MAPLE experiments. The typical surface morphology of thin films deposited by MAPLE technique is characterized by an aggregated structure, consisting of micrometer-sized particles [17,18,22,39,119]. It is worth noting that a larger specific surface area was proven to induce an enhanced bioactivity, able to promote osteoblast differentiation, as reported in case of hybrid organic-inorganic thin films deposited by MAPLE [120,121].…”
Section: Hybrid Dextran-iron Oxide Thin Filmsmentioning
confidence: 81%
“…iron oxide, pointing to good biocompatibility [18]. Moreover, in a similar study, Ciobanu et al [39] showed that Hep G2 cells adhered very well to thin films of Dextran-doped maghemite and exhibited a normal actin cytoskeleton, proving that these cells underwent normal cell cycle progression. As a result, the authors consider that hepatocytes adhered to hybrid thin films could be used as biosensors for different xenobiotics.…”
Section: Hybrid Dextran-iron Oxide Thin Filmsmentioning
confidence: 82%
See 1 more Smart Citation